Urgensi Penjelasan Keagamaan terhadap Keluarga Suspek Pasien Dalam Pengawasan (PDP) Covid-19 di RSU Pakuwon, Sumedang - Muhyidin, Asep; Rosyad, Rifki; Rahman, M. Taufiq; Huriani, Yeni (Hanifiya: Jurnal Studi Agama-Agama, 2020)
This study discusses religious explanations as a form of communication behavior among public relations officers at Pakuwon General Hospital, Sumedang. Here discussed how the adaptation of a hospital to the times, including an outbreak of a disease, such as Covid-19. With a qualitative approach and descriptive method, it is known that the hospital not only meets the health needs of patients, but also as a place of calm will be anxious about health problems. Due to the strong religious attitude, the religious explanation from the Public Relations also always accompanies the logic of explanation to patients, including about Covid-19. The need for existence is a major need during epidemics, where health and safety needs affect each other. The need for humanistic concern is the most important of the needs of interconnection; Interpersonal and family needs also increase. Here the religious explanation plays an important role because the society faced is also a religion-based society, namely Islam as the majority religion of Sumedang residents. It was found that the existence, linkages, and growth in clinical nurses need to coexist. Religious explanation is very helpful to meet the information needs so that communication between the hospital and the families of COVID-19 Patients Under Supervision (PDP) can be felt properly.